Relative Orientation Dependent on Dual Quaternions - Sheng, Qing H.; Shao, Sa; Xiao, Hui; Zhu, Feng; Wang, Qing; Zhang, Bin (Photogrammetric record, 2015)
A new approach to relative orientation based on dual quaternions is proposed. Dual quaternions are used to express a unified description of the relative position and orientation of two images in a stereopair. The coplanarity condition equation and its linearised model based on dual quaternions are established. According to the principle of least squares adjustment with constraints, a dual quaternion can be identified and the relative‐orientation parameters can then be obtained by a non‐linear transformation of the components of the dual quaternion. Experimental results show that the proposed approach is feasible and more reliable and efficient than the conventional approach based on Euler angles. Résumé Cet article propose une nouvelle approche de l'orientation relative basée sur les quaternions duaux. Ceux‐ci sont utilisés pour exprimer une description unique de la position relative et de l'orientation de deux images dans un couple stéréoscopique. L’équation de coplanarité est établie et linéarisée en utilisant des quaternions duaux. Selon le principe de l'ajustement par moindres carrés sous contraintes, un quaternion dual peut être identifié et une transformation non linéaire de ses composantes fournit alors les paramètres d'orientation relative. Les résultats expérimentaux confirment la faisabilité de l'approche proposée et montrent qu'elle est plus fiable et plus efficace que l'approche conventionnelle basée sur les angles d'Euler. Zusammenfassung Dieser Beitrag präsentiert einen neuen Ansatz zur Relativen Orientierung basierend auf dualen Quaternionen. Mit dualen Quaternionen wird eine einheitliche Beschreibung der relativen Position und Orientierung zweier Bilder eines Stereobildpaares beschrieben. Die Bedingungsgleichungen zur Koplanarität und ihr linearisiertes Modell, das auf dualen Quaternionen basiert, werden erstellt. Nach dem Prinzip der Kleinsten‐Quadrate‐Ausgleichung mit Bedingungen kann ein duales Quaternion ermittelt werden. Die Parameter der Relativen Orientierung können durch die nichtlineare Transformation der Komponenten des dualen Quaternions bestimmt werden. Die experimentellen Ergebnisse bestätigen, dass der vorgeschlagene Ansatz durchführbar und zuverlässiger und effizienter ist, als der konventionelle Ansatz basierend auf Euler'schen Winkeln. Resumen Se propone un nuevo enfoque de la orientación relativa basado en cuaternas duales. Los cuaterniones duales se utilizan para describir unificadamente la posición y orientación relativa de las imágenes de un par estereoscópico. Se establece el modelo linealizado de la ecuación de condición de coplanaridad parametrizada en cuaterniones duales. De acuerdo con el principio de ajuste de mínimos cuadrados con restricciones, puede ser identificado un cuaternión dual y, entonces, los parámetros de orientación relativa pueden obtenerse mediante una transformación no lineal de los componentes del cuaternión dual. Los resultados experimentales prueban que el enfoque propuesto es factible, más fiable y más eficiente que el enfoque convencional basado en ángulos de Euler. 摘要 本文提出了一种基于对偶四元数的相对定向新方法。采用对偶四元数统一描述立体像对中左右影像的相对位置和姿态,建立了基于对偶四元数的共面条件方程及其线性化模型,根据附有约束条件的最小二乘平差,求解对偶四元数,并通过其与相对定向元素之间的非线性变换,得到相对定向元素。实验结果表明,本文提出的方法是正确可行的,并且相比于传统欧拉角法,对偶四元数法相对定向对初值依赖性小,更加稳定可靠,并且能够有效减少迭代次数,提高解算效率。